Identification of marbling-related candidate genes in M. longissimus dorsi of high- and low marbled Hanwoo (Korean Native Cattle) steers - Lee, S.H. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Cho, Y.M. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Lee, S.H. (National Institute of Animal Science, RDA, Cheonan, Republic of Korea); Kim, B.S. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Kim, N.K. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Choy, Y.H. (National Institute of Animal Science, RDA, Pyeongchang, Republic of Korea); Kim, K.H. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Yoon, D.H. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Im, S.K. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Oh, S.J. (National Institute of Animal Science, RDA, Suwon, Republic of Korea); Park, E.W. (National Institute of Animal Science, RDA, Suwon, Republic of Korea), E-mail: pewkys@rda.go.kr (BMB reports, 2008)
This study was conducted to identify marbling-related candidate genes in M. longissimus dorsi of high- and low-marbled Hanwoo. The longissimus dorsi muscles were selected for gene expression from eight Hanwoo, steer carcasses based on crude fat content In the analysis of variance, gene expression of five candidate genes, FABP4, SCD, PPAR γ, Titin and Nebulin was determined to be significantly different between high- and low-marbled Hanwoo steers (P less than 0.0001). The Pik-4 and CaMK Ⅱ genes were also shown to have a significant effect on crude fat content (P less than 0.01). In the analysis of the differential expression between high- and low marbled groups, FABP4 gene expression was approximately 2 times higher in the high marbled group relative to the low marbled group. However, the PPAR γ and SCD gene were highly expressed in the low marbled group. In addition, Titin and Nebulin were highly expressed in the low marbled group when placed under relatively high shear force. Finally, the Pik-4 and CaMK Ⅱ gene also displayed a high expression pattern in the low marbled group.